2020
DOI: 10.3991/ijet.v15i20.16683
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Lecture and Interactive Methods on Student’s English Competency

Abstract: The current research deals with the perceptions of non-native students at a university college in Oman on the use of the lecture and interactive methods in teaching English. The aim is to find out the method which may assist satisfactorily in improving students’ Eng-lish language competency in terms of skills, developing their cognitive abilities and enhancing their personal growth. This study employs the quantitative approach through conducting and analyzing students’ questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…Each characteristic of Allport's attitude theory also showed its own concept but served as a unit of attitude. Taat, Abdulbaki, and Al-Saqqaf [35] found that positive interaction between the teachers with the students will foster high level of academic attitude among the students. Therefore, attitudes as part of an individual's personality is as a result of behavioral influences which are related to the individual himself.…”
Section: Student Academic Attitudementioning
confidence: 99%
“…Each characteristic of Allport's attitude theory also showed its own concept but served as a unit of attitude. Taat, Abdulbaki, and Al-Saqqaf [35] found that positive interaction between the teachers with the students will foster high level of academic attitude among the students. Therefore, attitudes as part of an individual's personality is as a result of behavioral influences which are related to the individual himself.…”
Section: Student Academic Attitudementioning
confidence: 99%
“…As long as the question is only at the lower order thinking level, the teacher will have difficulty evaluating students' achievement, and their thinking skills will not develop. However, when the questions are more inquiry-based, communication between students can be more intensive, and their critical thinking skills can be more developed (Biggers, 2018;Matra, 2014;Taat et al, 2020).…”
Section: Analysis Of Communication Patterns Based On the Appearance Of Important Words Spoken By Teachers And Studentsmentioning
confidence: 99%
“…Competence is a description of the main skills, knowledge, abilities and attitudes needed to achieve effective performance in work [5]. According to Lawler in [6], competence is the capacity of organisms to interact effectively with the environment.…”
Section: Competencementioning
confidence: 99%